2004
DOI: 10.1111/j.0105-6263.2004.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of pregnancy by intrauterine insemination using CASA estimates and strict criteria in patients with male factor infertility

Abstract: This study was performed to predict pregnancy by intrauterine insemination (IUI) using computer-aided sperm analysis (CASA) estimates and strict criteria in patients with male factor infertility. IUI was performed in 682 cycles on 160 male factor infertile patients. Semen examinations were carried out by CASA and strict criteria before and after sperm preparation using continuous-step density gradient centrifugation. Receiver operating characteristics (ROC) curves were constructed for assessment of the effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 31 publications
5
33
3
1
Order By: Relevance
“…Das et al achieved pregnancy rates of 7.47%, 9 comparable to 8.2% achieved by Steures et al 13 and 9.2% reported by Iberico et al 14 Higherconception rates of 18% were recorded by Agarwal et al 15 from AIIMS which however was lower than the pregnancy rates of 20.83% achieved in our set up. The pregnancy rate per couple was 31.64% in our study and was slightly more than 28.1% reported by Shibahara et al 16 Ovarian stimulation by Clomiphene citrate (CC) and IUI remains the first choice treatment for ovulatory dysfunction, unexplained infertility, endometriosis, male subfertility with pregnancy rate averaging 40.91% pregnancies. Pregnancy rates as high as 40.91% have been seen with COH/IUI when it is the primary modality of treatment especially in cases of unexplained infertility, ovulatory dysfunction and endometriosis.…”
supporting
confidence: 40%
“…Das et al achieved pregnancy rates of 7.47%, 9 comparable to 8.2% achieved by Steures et al 13 and 9.2% reported by Iberico et al 14 Higherconception rates of 18% were recorded by Agarwal et al 15 from AIIMS which however was lower than the pregnancy rates of 20.83% achieved in our set up. The pregnancy rate per couple was 31.64% in our study and was slightly more than 28.1% reported by Shibahara et al 16 Ovarian stimulation by Clomiphene citrate (CC) and IUI remains the first choice treatment for ovulatory dysfunction, unexplained infertility, endometriosis, male subfertility with pregnancy rate averaging 40.91% pregnancies. Pregnancy rates as high as 40.91% have been seen with COH/IUI when it is the primary modality of treatment especially in cases of unexplained infertility, ovulatory dysfunction and endometriosis.…”
supporting
confidence: 40%
“…Thus, we found that activity of a4 is necessary for sperm total and progressive motility, straight line, curvilinear, and average path velocities, lateral head displacement, beat cross frequency, and linearity. The alterations in the parameters of sperm motility that we have studied have been used as important predictors of male fertility in patients and for IVF purposes (Moore & Akhondi 1996, Larsen et al 2000, Shibahara et al 2004. Based on these reports, the extent of the reduction in the various parameters of sperm movement that we obtained after treatment with 10 K6 M ouabain is expected to interfere with normal male fertility (Moore & Akhondi 1996, Larsen et al 2000, Shibahara et al 2004.…”
Section: Discussionmentioning
confidence: 97%
“…The alterations in the parameters of sperm motility that we have studied have been used as important predictors of male fertility in patients and for IVF purposes (Moore & Akhondi 1996, Larsen et al 2000, Shibahara et al 2004. Based on these reports, the extent of the reduction in the various parameters of sperm movement that we obtained after treatment with 10 K6 M ouabain is expected to interfere with normal male fertility (Moore & Akhondi 1996, Larsen et al 2000, Shibahara et al 2004. Therefore, our results indicate that activity Na,K-ATPase a4 isoform mechanisms of action of the Na,K-ATPase a4 polypeptide widely influences sperm movement, and suggest that this isoform is important to support motility and fertility of the male gametes.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, two studies favored fourth percentiles [12,36] . Only one study indicated a positive association at a cutoff of 15.5% [38] , with significantly higher pregnancy rates when morphologically normal spermatozoa reached that level.…”
Section: Discussionmentioning
confidence: 99%